GRAMMARIANS’ UNDERSTANDING VARIETY TO THE TEXT OF SEBWAYH - Dr. Omar ThabitYousufMajeed Al-Jubouri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Praise be to God, Lord of the Worlds, and may peace and blessings be upon us Muhammad and upon all his family and companions. And after the people of Basra differed among themselves - just as they disagreed with Kufa - and among the reasons for this was their disagreement in the interpretation of Sibawayh’s statement or outlining it. There are statements that Sibawayh mentioned in his book possible for more than one explanation for this. This is due to the interest of the grammarians in the book because of its value in the grammar lesson.